Health Impacts of Low-Dose Ionizing Radiation: Current Scientific Debates and Regulatory Issues. Issue 3 (18th September 2018) - Vaiserman, Alexander; Koliada, Alexander; Zabuga, Oksana; Socol, Yehoshua
Health impacts of low-dose ionizing radiation are significant in important fields such as X-ray imaging, radiation therapy, nuclear power, and others. However, all existing and potential applications are currently challenged by public concerns and regulatory restrictions. We aimed to assess the validity of the linear no-threshold (LNT) model of radiation damage, which is the basis of current regulation, and to assess the justification for this regulation. We have conducted an extensive search in PubMed. Special attention has been given to papers cited in comprehensive reviews of the United States (2006) and French (2005) Academies of Sciences and in the United Nations Scientific Committee on Atomic Radiation 2016 report. Epidemiological data provide essentially no evidence for detrimental health effects below 100 mSv, and several studies suggest beneficial (hormetic) effects. Equally significant, many studies with in vitro and in animal models demonstrate that several mechanisms initiated by low-dose radiation have beneficial effects. Overall, although probably not yet proven to be untrue, LNT has certainly not been proven to be true. At this point, taking into account the high price tag (in both economic and human terms) borne by the LNT-inspired regulation, there is little doubt that the present regulatory burden should be reduced.